Adversity Quotient bagi Anak-Anak Sejak Dini - Suwarni Baigar (SANCTUM DOMINE: JURNAL TEOLOGI, 2018)
Children are an important part of life, as the successor to future generations of the family and the nation. To make them generations of very, of course, there are many factors that could be done by the parents (family), institutions educational, social agencies and institutions of religion (spirituality), and so forth. One of that way to prepare them to be the generation of quality in the future is to train one part of their intelligence, intelligence of children adversity, which was first proposed by Paul G. Stoltz. By training and guiding intelligence of adversity of child, future children will have a strong foundation in the face of life's difficulties, challenges, and even remain standing and struggling forward when they will fail.